2018
DOI: 10.3389/fncel.2018.00143
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Plasticity of Spinal Lamina II GABA Neurons Is Induced by Sciatic Nerve Chronic Constriction Injury in Mice

Abstract: Mice with transgenic insertion of code for enhanced green fluorescent protein (EGFP) at the locus for glutamic acid decarboxylase 67 (GAD67), one of two key enzymes for the synthesis of γ-aminobutyric acid (GABA) were used to test whether the morphological properties of these neurons show plasticity with nerve injury. Physiological properties and the delivery of intracellular label to EGFP-expressing lamina II neurons was done using whole-cell patch-clamp in spinal cord slices from sham and chronic constrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
21
0
2
Order By: Relevance
“…While these results are the first of their kind to demonstrate cytoarchitectural changes in models of chronic migraine, alterations in neuronal plasticity have been described previously in models of neuropathic pain. A mouse model of chronic constriction injury of the sciatic nerve reduced neurite length in GABA neurons within lamina II of the spinal cord [50]. Another group observed that following spared nerve injury, there were decreases in the number of branches and neurite length of hippocampal neurons but increases in spinal dorsal horn neurons [51].…”
Section: Discussionmentioning
confidence: 99%
“…While these results are the first of their kind to demonstrate cytoarchitectural changes in models of chronic migraine, alterations in neuronal plasticity have been described previously in models of neuropathic pain. A mouse model of chronic constriction injury of the sciatic nerve reduced neurite length in GABA neurons within lamina II of the spinal cord [50]. Another group observed that following spared nerve injury, there were decreases in the number of branches and neurite length of hippocampal neurons but increases in spinal dorsal horn neurons [51].…”
Section: Discussionmentioning
confidence: 99%
“…pentobarbital sodium, and the sciatic nerve exposed by blunt dissection of the biceps femoris muscle, and dissected and freed proximal to the sciatic trifurcation. Three 4-0 chromic catgut ligatures 45 48 were loosely tied around the sciatic nerve until the rat’s hind limb briefly twitched. Both sides of the sciatic nerve were handled using the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis implicates the downregulation of the chloride ion transporter KCC2 following peripheral nerve injury [ 112 115 ], brought about by the release of brain-derived neurotrophic factor (BDNF) from axotomized afferents [ 116 , 117 ]. A reduction of KCC2 leads to disruption in chloride equilibrium, and this reduces the efficacy of inhibition mediated by the release of GABA and glycine in pain-transmitting neurons, whereas others have proposed that the reduced excitability of inhibitory interneurons and/or loss of their synaptic inputs are additional contributing factors [ 118 120 ].…”
Section: Cellular Basis and Behavioral Consequences Of Spinal Disinhimentioning
confidence: 99%